The role of tranexamic acid for infection prevention after fracture fixation - Benjumea-Carrasco, Antonio; Guembe, María; Díaz-Navarro, Marta; Muñoz, Patricia; Vaquero-Martin, Javier; Chana-Rodriguez, Francisco (Injury, 2024)
Despite the measures employed, fracture-related infections remain a concern after fracture fixation worldwide. Recently, the role of tranexamic acid as a protective drug against postsurgical infections in joint replacement and orthopedic trauma surgery has been proposed, where tranexamic acid has been associated with less surgical wounds complications and infectious complications including periprosthetic joint infection. The mechanism through which tranexamic acid exerts a protective effect against peri-implant infection is still the subject of debate. Although some authors hypothesize an indirect effect inhibiting the formation of postoperative hematoma, there are several studies that show a direct antibacterial effect of the drug against the capacity of bacterial aggregation, even avoiding biofilm formation, favoring the immune response of the host and the action of antibiotics. The purpose of this narrative review is to show the current role of tranexamic acid in orthopedic trauma, specifically its relationship with the prevention of infections related to implants.